Association between SATB2 gene polymorphism and cleft palate only risk in eastern Guangdong population and a meta-analysis - Zhang, Wancong; Tan, Linwang; Xing, Yue; Zhao, Hanxing; Shi, Lungang; Zhou, Jianda; Lang, Xing; Cai, Jianxiong; Tang, Shijie (Cellular and Molecular Biology, 2018)
To characterize the associations between the cleft palate (CPO) and single nucleotide polymorphisms (SNPs) of special AT-rich sequence-binding protein 2 (SATB2). We recruited 241 CPO and performed a case-control study with 242 controls. Concurrently, 103 of the patients and their normal parents were recruited to perform a case-parent trio study. Sixteen selected SNPs were genotyped. Furthermore, A meta-analysis was used to enhance the robustness of our conclusions. The case-control study provided no support for the hypothesis that any of the 16 selected SNPs played a significant role in CPO. In the meta-analysis, we also did not find that the SATB2 was associated with nonsyndromic cleft palate risk, in Asians or in Caucasians. The 16 selected SNPs do not contribute to the development of CPO.